(Im)Politeness As Persuasion In Ryan Coogler’s Sinners - Wahyudi, Ardi; Yunus, Reski Yusrini Islamiah; Juanda (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
The goal of this research is to describe usage of polite and impolite language in the film Sinners, directed by Ryan Coogler, as a means of persuasion. Brown and Levinson’s theory of politeness and Culpeper and Hardaker’s theory of impoliteness was used as the foundational theory of this study. Dialogue and character action from four scenes were analyzed with the qualitative descriptive method to explain how the first party tried to get the second party to do what was asked of them. Results indicate that a varied mix of politeness and impoliteness are utilized as a means of persuasion. Multiple times the first party would often start with polite strategies such as noticing the second party’s interests and quickly devolve into impoliteness such as the bald on record impoliteness superstrategy like. threats as a way to expedite the negotiations with the second party. This shows that a speaker that can adapt strategy usage to the mood of the situation is pivotal to the persuasiveness of the speaker, even if impoliteness like the promise of violence is part of said strategy. This also shows that negotiations can happen as a one sided persuasion battle or a two sided conversation with mutually exclusive goals. Thus this research adds to the body of previous research into how politeness is used as a tool of persuasion, while also offering new insight into how mixing politeness and impoliteness can be critical to persuasion. Keywords: Politeness, Impoliteness, Persuasion